Private self-awareness, state boredom, and snack purchases desire: the moderating role of self-control - Bin Peng; Nuo Liu; Kunying Zhang; Sihua Xu (Cogent Psychology)
Existing literature suggests a potential link between private self-awareness and purchase decisions, though the evidence supporting this claim remains limited. Moreover, the role of private self-awareness as a predictor of overall purchase desire has been largely underexplored, particularly in the context of negative emotions and self-control in contemporary consumer behavior. This study investigates the moderated mediation effects of self-control, via state boredom, on the relationship between private self-awareness and snack purchase desire. Participants were recruited from a university in Shanghai through online platforms, and data were analyzed to explore these relationships. Those in the self-awareness priming group completed a task designed to enhance self-awareness before responding to state boredom and self-control scales, while the control group completed only the state boredom and self-control scales. Subsequently, participants rated their likelihood of purchasing snacks depicted in images of four snack options. The findings reveal that private self-awareness positively influences snack purchase desire, with state boredom mediating this relationship and self-control acting as a moderator. These results have significant implications for emotional marketing strategies, particularly in understanding how self-control and emotional states impact consumer behavior. This research contributes to existing literature by elucidating the complex dynamics between self-awareness, emotional states, and purchasing behavior, offering both theoretical insights and practical applications for marketers.